Analisis Penggunaan Website Berbasis AI dalam Mengerjakan Tugas Akademik pada Mahasiswa Pendidikan Agama Islam Universitas Negeri Padang - Alfurqan, Muhammad Hadli; Wirdati, Wirdati (ISLAMIKA, 2024)
This study explores the use of AI-based websites by Islamic Education students at Universitas Negeri Padang in completing academic tasks. Using a qualitative method with a case study approach, data were collected through interviews, observations, and documentation, and then analyzed to ensure their validity. The results show that websites such as ChatGPT, Perplexity, and Gemini.ai are used to answer academic questions, search for scientific references, and analyze images and texts. However, challenges such as the limitations of AI understanding in religious studies, reliance on technology, and information reliability remain issues. Students use AI for structured tasks by obtaining topic explanations and scientific references, and for independent tasks such as studying course materials, creating presentations, translating languages, and answering discussion questions. The use of AI has proven beneficial, but existing challenges need to be addressed to maximize its potential.